Analisis Pengetahuan dan Keterampilan Kesiapan Kebencanaan pada Guru SMA Negeri 1 Kalianda, Lampung Selatan - M. Atho Illah Daimul Ichsan; Muhammad Nurwahidin; Ratna Widiastuti (Jurnal Humaniora dan Ilmu Pendidikan, 2023)
Disaster preparedness actually focuses on preparedness and prevention, so it's not just when a disaster has occurred. In this phase, knowledge and skills are needed related to understanding that focuses on knowledge to survive as a survivor and to know the abilities possessed by each individual to deal with the disaster that will occur. Purpose: This study aims to provide a descriptive description of the knowledge and skills of teachers at SMAN 1 Kalianda, South Lampung. Methodology: The research method in this study is a quantitative method with a descriptive approach. The data collection technique used in this study was using an open questionnaire. This study uses descriptive statistical analysis with percentages, the presentation of the data analyzed using descriptive quantitative research methods. Results: Based on the results of the analysis conducted by researchers to 66 teachers as respondents in SMA Negeri 1 Kalianda, it can be said that teachers have a level of knowledge and skills of disaster preparedness in the medium and high categories.